Determination of the Presence of Three Antimicrobials in Surface Water Collected from Urban and Rural Areas - Alberto Cepeda; Carlos M. Franco Abuín; Beatriz I. Vázquez; Jose M. Miranda; Carolina Nebot; Alejandra Iglesias (MDPI AG, 2013)
Due to the continuous release of antimicrobials into the environment, the aim of this study was to compare the frequency of detection of sulfamethazine, sulfamethoxypyridazine and trimethoprim in surface water collected from urban and rural areas in Northwestern Spain. A monitoring study was conducted with 314 river water samples analyzed by high-performance liquid chromatography coupled to tandem mass spectrometry. The results indicated that 37% of the samples contained residues of at least one of the investigated antimicrobials, and every sampling site yielded positive samples. At sites located near the discharge points of wastewater treatment plants and near the collection point of a drinking-water treatment plant, more than 6% of the samples were positive for the presence of antimicrobial residues.